Global macro risks in currency excess returns - Kimberly A. Berg; Nelson C. Mark (Bank of Canada, 2016)
We study a cross section of carry-trade-generated currency excess returns in terms of their exposure to global fundamental macroeconomic risk. The cross-country high-minuslow (HML) conditional skewness of the unemployment gap—our measure of global macroeconomic uncertainty—is a factor that is robustly priced in currency excess returns. A widening of the HML gap signifies increasing divergence, disparity and inequality of economic performance across countries.
Keywords: E21; E43; F31; G12; 330; Interest rates; Exchange rates; Asset pricing